Rizki Amalia Putri PENGARUH JOB STRESS TERHADAP KINERJA KARYAWAN DI UNIVERSITAS NAHDLATUL ULAMA SIDOARJO (UNUSIDA) DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING : Program Studi Manajemen, Universitas Nahdlatul Ulama Sidoarjo *e-mail: amelia.puteri88@gmail.com - Rizki Amalia Putri (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Competition and the demands of professionalism are increasingly high, causing many problems that must be faced by employees in a work environment that has the potential to cause anxiety. This study aims to analyze the effect of job stress on the performance of employees of Nahdlatul Ulama Sidoarjo University (UNUSIDA) with job satisfaction as an intervening variable. This study uses primary research data. The method of data collection is done by distributing questionnaires and documentation as an interview tool. The results obtained are there are negative effects between job stress on performance, so that if the lower job stress, the performance will increase as well. Then there is a negative influence between job satisfaction on work performance, so that if the higher job satisfaction, then the performance will increase. And there is a negative influence between job stress on job satisfaction, so if the lower job stress, then satisfaction will increase.